Pengaruh Sosialisasi Legalitas Usaha Terhadap Pengembangan Kewirausahaan Di Desa Kedungdalem Kabupaten Probolinggo - Afifah Ulul Azmi; Indah Respati Kusumasari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Fluency in entrepreneurship is certainly an important point in running a business or developing a business. One of them can be by following and complying with the completeness and preparation for entrepreneurship. Business license number (NIB) is one of the requirements for completeness of documents and development in entrepreneurship. This study aims to analyze the socialization of the Business Permit Number (NIB) and its impact on entrepreneurship development in Kedungdalem Village, Probolinggo Regency. The government's goal with the NIB policy is to make it easier to get business licenses and encourage the growth of entrepreneurship.